A Reduced Astrocyte Response to β-Amyloid Plaques in the Ageing Brain Associates with Cognitive Impairment - Mathur, Ryan (PLoS One, 2015)
AIMS: β-amyloid (Aβ) plaques are a key feature of Alzheimer’s disease pathology but correlate poorly with dementia. They are associated with astrocytes which may modulate the effect of Aβ-deposition on the neuropil. This study characterised the astrocyte response to Aβ plaque subtypes, and investigated their association with cognitive impairment. METHODS: Aβ plaque subtypes were identified in the cingulate gyrus using dual labelling immunohistochemistry to Aβ and GFAP(+) astrocytes, and quantitated in two cortical areas: the area of densest plaque burden and the deep cortex near the white matter border (layer VI). Three subtypes were defined for both diffuse and compact plaques (also known as classical or core-plaques): Aβ plaque with (1) no associated astrocytes, (2) focal astrogliosis or (3) circumferential astrogliosis. RESULTS: In the area of densest burden, diffuse plaques with no astrogliosis (β = -0.05, p = 0.001) and with focal astrogliosis (β = -0.27, p = 0.009) significantly associated with lower MMSE scores when controlling for sex and age at death. In the deep cortex (layer VI), both diffuse and compact plaques without astrogliosis associated with lower MMSE scores (β = -0.15, p = 0.017 and β = -0.81, p = 0.03, respectively). Diffuse plaques with no astrogliosis in layer VI related to dementia status (OR = 1.05, p = 0.025). In the area of densest burden, diffuse plaques with no astrogliosis or with focal astrogliosis associated with increasing Braak stage (β = 0.01, p<0.001 and β = 0.07, p<0.001, respectively), and ApoEε4 genotype (OR = 1.02, p = 0.001 and OR = 1.10, p = 0.016, respectively). In layer VI all plaque subtypes associated with Braak stage, and compact amyloid plaques with little and no associated astrogliosis associated with ApoEε4 genotype (OR = 1.50, p = 0.014 and OR = 0.10, p = 0.003, respectively). CONCLUSIONS: Reactive astrocytes in close proximity to either diffuse or compact plaques may have a neuroprotective role in the ageing brain, and possession of at least one copy of the ApoEε4 allele impacts the astroglial response to Aβ plaques.